Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve for x:
(x − 2)(x + 7) = −1+2x


Sagot :

Answer:

(-3±√61)÷2

Step-by-step explanation:

First we expand the brackets to give us :

x²+5x-14 = -1 +2x

Now we make this into the quadratic format (x²+ax+b=0) by subtract -1 and 2x from both sides :

x²+3x-13 = 0

This quadratic cannot be factorized so we must use the quadratic formula :

x = [tex]\frac{-b+\sqrt{b^{2} -4ac} }{2a}[/tex]   or   x = [tex]\frac{-b-\sqrt{b^{2} -4ac} }{2a}[/tex]

a = 1 , b = 3 , c = -13

Now we simplify as much as possible by first substituting values known :

x = [tex]\frac{-3+\sqrt{3^{2} -4(1)(-13)} }{2(1)}[/tex]    or   x = [tex]\frac{-3-\sqrt{3^{2} -4(1)(-13)} }{2(1)}[/tex]

Now we evaluate the exponent :

x = [tex]\frac{-3+\sqrt{9 -4(1)(-13)} }{2(1)}[/tex]   or     x = [tex]\frac{-3-\sqrt{9 -4(1)(-13)} }{2(1)}[/tex]

Now we multiply the numbers :

x = [tex]\frac{-3+\sqrt{9 +52 } }{2(1)}[/tex]    or   x = [tex]\frac{-3-\sqrt{9 +52 } }{2(1)}[/tex]

Now we add the numbers :

x = [tex]\frac{-3+\sqrt{61} }{2(1)}[/tex]   or   x = [tex]\frac{-3-\sqrt{61} }{2(1)}[/tex]

Now we multiply the denominator:

x = [tex]\frac{-3+\sqrt{61} }{2}[/tex]   or   x = [tex]\frac{-3-\sqrt{61} }{2}[/tex]

So our final answer is (-3±√61)÷2

Hope this helped and 5 stars, a heart and brainliest please

We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.